Review of light activated antibacterial nanomaterials in the second biological window - Suresh Thangudu; Chia-Hao Su (Journal of Nanobiotechnology)
Abstract Bacterial infections continue to pose a major threat to public health, contributing to high mortality rates worldwide. The growing ineffectiveness of conventional antibiotics has created an urgent need for alternative solutions. Nanomaterials (NMs) have emerged as a promising approach to combating bacterial infections due to their unique physicochemical properties, and extensive research has been conducted to address this crisis, yielding notable results. However, challenges such as limited light absorption and inherent cytotoxicity remain significant concerns. Furthermore, the clinical adoption of single-mode phototherapy is often restricted by the shallow tissue penetration of traditional light sources. The second biological window (NIR-II, 950–1450 nm) offers a groundbreaking opportunity for therapeutic and diagnostic applications by enabling deeper tissue penetration. As a result, growing research efforts are dedicated to developing NIR-II activated photosensitizers and nanomaterials to overcome challenges such as poor light absorption, limited tissue penetration, and suboptimal activation. Despite significant advancements, a comprehensive review of antibacterial nanomaterials specifically designed for the NIR-II window is still lacking in literature. This review aims to fill that gap by discussing the latest advancements, challenges, and potential of light-activated antibacterial nanomaterials within the BW-II region. The goal is to enhance understanding and guide the development of more efficient nanomaterials for future biomedical and clinical applications.